Toward an Inclusive Creative Writing Threshold Concepts to Guide the Literary Curriculum - Adsit, Janelle (Bloomsbury Academic, 2017)
The creative writing workshop has existed since the early part of the 20th century, but does it adequately serve the students who come to it today? While the workshop is often thought of as a form of student-centered pedagogy, it turns out that workshop conversations serve to marginalize a range of aesthetic orientations and the cultural histories to which they belong. Given the shifting demographics of higher education, it is time to re-evaluate the creative writing curriculum and move literary writing pedagogy toward a more inclusive, equitable model. Toward an Inclusive Creative Writing makes the argument that creative writing stands upon problematic assumptions about what counts as valid artistic production, and these implicit beliefs result in exclusionary pedagogical practices. To counter this tendency of creative writing, this book proposes a revised curriculum that rests upon 12 threshold concepts that can serve to transform the teaching of literary writing craft. The book also has a companion website www.criticalcreativewriting.org offering supplemental materials such as lesson plans and course materials.